Variability of Selected Clinical and Haematological Indices in Young Stallions During 100-Day Performance Test - Janicki Bogdan; Kochowicz Anna; Buzała Mateusz; Krumrych Wiesław (Journal of Veterinary Research, 2013)
The study was conducted on 20 clinically healthy stallions, aged 3-4 years. The evaluation of the degree of adaptation of stallions to exercise loads in the course of a 100-d training programme was conducted three times: (I) - on the 1st d of training, (II) - on the 46th d of training, and (III) - on the 97th d of training. Rectal temperature (T) and number of heart and respiratory rates were measured. Blood was sampled before exercise (1), after exercise (2), and 30 min after rest (3). The following indices were determined in the blood: concentration of haemoglobin, haematocrit level, number of red blood cells, white blood cells, lymphocytes, neutrophils, eosinophils, basophils, monocytes, and platelets. Post-exertion changes in the evaluated indicators showed moderate intensity to the applied loads with respect to functional potential of tested horses. The effect of the standard 100-d training was to stimulate the body's adaptation to functional tasks, which was evidenced, among others, by lower variability of post-exertion T and the number of red blood cells. The highest T increase was found at the beginning of the programme (about 2.1%), whereas during the subsequent studies (II and III) it was significantly (P<0.05) lower (0.98% and 0.84%, respectively). The variability in red blood cell count in the course of training showed a downward trend (16.4%, 13.7%, and 11.0%, respectively). The results confirm the relatively low exercise loads and good health of young stallions during the 100-d performance test.